Blood Pressure Indices and Associated Risk Factors in a Rural West African Adult Population: Insights from an AWI-Gen Substudy in Ghana. (27th April 2020) - Agongo, Godfred; Nonterah, Engelbert A.; Amenga-Etego, Lucas; Debpuur, Cornelius; Kaburise, Michael B.; Ali, Stuart A.; Crowther, Nigel J.; Ramsay, Michèle; Oduro, Abraham R.
Abstract : Systolic (SBP) and diastolic blood pressure (DBP) are commonly used for cardiovascular disease (CVD) risk prediction, and pulse pressure (PP) and mean arterial blood pressure (MAP) can provide additional information. It is therefore important to understand the factors associated with these cardiovascular risk markers. This cross-sectional study involved 1839 men and women aged 40–60 years. Data on SBP, DBP, MAP, PP, sociodemography, lifestyle, anthropometry, and lipids were collected. Gender-stratified linear regression analyses were performed to determine the association between log-transformed blood pressure indices and the study variables. Age was associated with all measured blood pressure indices (p < 0.001 ) among men and women. Men had higher SBP (p = 0.007 ) and PP (p < 0.001 ) than women. Nankana ethnicity was associated with higher PP levels (p < 0.005 ) in the total population. Vendor meal consumption among women was associated with higher PP levels (p < 0.05 ). Fruit intake among men was associated with lower PP levels (p < 0.05 ). Currently unmarried women had higher SBP (p < 0.005 ), DBP (p < 0.05 ), MAP (p < 0.005 ), and PP (p < 0.005 ) than currently married women. Pesticide exposure was negatively associated with SBP (p < 0.005 ), DBP (p < 0.005 ), MAP (p < 0.005 ), and PP (p < 0.05 ) among women. Increased subcutaneous fat was associated with DBP (p < 0.005 ) and MAP (p < 0.05 ) among women. Among men, hip circumference was associated with higher DBP and MAP (p < 0.05 for both associations), subcutaneous fat associated with higher SBP (p < 0.005 ), DBP (p < 0.001 ), and MAP (p < 0.001 ) and visceral fat was associated with higher PP (p < 0.05 ). In the total population, visceral fat was associated with higher DBP (p < 0.05 ) and MAP (p < 0.001 ). High-density lipoprotein cholesterol was positively associated with SBP (p < 0.005 ), DBP (p < 0.005 ), and MAP (p < 0.001 ) for women and positively associated with SBP, DBP, and MAP (p < 0.001 for all three) and PP (p < 0.05 ) for men. The association of blood pressure indices with modifiable risk factors suggests that targeted health interventions may reduce CVD risk in this population.